“Ordinance No. 8.” Los Angeles Herald, April 12, 1889, p. 7. Ordinance No. 8—An Ordinance to Amend an Ordinance Entitled an “Ordinance Regulating the Carrying of Deadly or Dangerous Weapons,” §§ 1–2. Approved April 10, 1889; In Force April 12, 1889. Volume 32, Number 10. (Los Angeles, CA) - (:unkn) unknown (General Publisher, 1889)
Prohibited concealed carry of any dirk, Bowie-knife, sword-cane, pistol, revolver, or any other dangerous or deadly weapon.
--
Keywords: CARRY - CONCEALED